Adhesive composition for decorative sheet, decorative sheet, decorative structure and method for manufacturing the same
Patent Information
- Application Number
- JP2023142361
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-01
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2043-09-01
AI Technical Summary
【0013】 本発明により、成形品の加飾において、凹凸部を有する複雑な形状に追従し、かつ低極性被着体に対する粘着力、透明性、成形品に優れた外観を付与できる、加飾シート用粘着剤組成物、加飾シート、加飾構造体およびその製造方法の提供をすることが可能となる。 所定の(メタ)アクリル酸エステル共重合体(A)と硬化剤(B)と粘着付与樹脂(C)を含有する粘着剤組成物で粘着層を形成するとき、成形品の加飾において、凹凸部を有する複雑な形状に追従し、かつ低極性被着体に対する粘着力、透明性、成形品に優れた外観を付与できることを知得した。
Smart Images

Figure 2025035367000001 
Figure 2025035367000002 
Figure 2025035367000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a pressure-sensitive adhesive composition for a decorative sheet, a decorative sheet, a decorative structure, and a method for producing the same. [Background technology]
[0002] Decorating the exterior surface of molded products such as automobile interior and exterior parts, keyboards, home appliances, smartphones, housing materials, furniture, musical instruments, and Shinkansen window frames and walls is being done with decorative films (decorative sheets) to improve the appearance quality of the molded products. Methods for decorating molded products with three-dimensional shapes using decorative sheets include insert molding, in-mold molding, vacuum molding, and vacuum-compressed air molding.
[0003] The insert molding method is a method in which a decorative sheet is first formed into a specified shape and inserted into a mold, and then heated molten resin is pressurized and poured into the mold for injection molding, and then cooled and solidified to produce a decorated molded product in which the decorative sheet and the molded product are integrated. In-mold molding is a method of producing a decorated molded product by setting a film with a printed design in a mold with a release layer between them, injecting heated molten resin and allowing it to cool and solidify, and then peeling off the film to transfer the design. In this way, in the insert molding method and the in-mold molding method, the molded article is decorated at the same time as it is molded, and a design is formed on the exterior surface of the molded article.
[0004] On the other hand, vacuum forming is a method in which the decorative sheet is softened by applying heat and the air between the decorative sheet and the molded product is removed from the molded product side, creating a near-vacuum state and adhering the decorative sheet to the molded product. In addition, the vacuum and pressure molding method creates a similar vacuum state, and then applies air pressure from the decorative sheet side above the molded product to adhere the decorative sheet to the molded product. Thus, the vacuum forming method and the vacuum pressure forming method are methods for decorating a molded product by attaching a decorative sheet at room temperature after the molded product is completed and heating it. In other words, the decorative sheet is attached to the exterior surface of the molded product in a separate operation from the molding of the molded product, so that a single device can be used to attach the decorative sheet to molded products of various shapes. In addition, the vacuum forming method and the vacuum pressure forming method are widely used because they allow continuous coating from the front to the back of the molded product edge, i.e., wrap-around coating, which is difficult to achieve with the in-mold molding method and the like.
[0005] Compared to acrylonitrile-butadiene-styrene resin (hereinafter also referred to as ABS resin), which is commonly used as an adherend material, polypropylene resin (hereinafter also referred to as PP resin) has a low specific gravity and excellent thermoformability. For this reason, in recent years, PP resin has been increasingly used as an adherend to reduce weight and improve processability. An adhesive is used to attach the decorative sheet to the adherend, and there is a growing need for an adhesive that can attach the decorative sheet to low-polarity materials such as PP resin.
[0006] Patent Document 1 discloses a molded article obtained by bonding, by heat and pressure, an adhesive film having an adhesive layer containing a (meth)acrylic polymer containing carboxy groups in a specific ratio and having a glass transition temperature of 25°C or lower, and a (meth)acrylic polymer containing amino groups in a specific ratio and having a glass transition temperature of 75°C or higher.
[0007] Patent Document 2 discloses a decorative molding film including an adhesive layer, which is characterized by containing a copolymer of methyl acrylate and an alkyl acrylate ester containing an alkoxy group having four carbon atoms, and 1 to 40 parts by weight of an alkyl (meth)acrylate ester having a glass transition temperature of 115°C or lower and a weight average molecular weight of 5,000 to 100,000 per 100 parts by weight of the copolymer. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2009-035588 A [Patent Document 2] JP 2017-132205 A Summary of the Invention [Problem to be solved by the invention]
[0009] Usually, when a decorative sheet is attached to a molded product by vacuum forming or vacuum / pressure forming, it is expected that the decorative molded product will be used in various environments, so it is important that the sheet conforms to the complex shape with uneven parts, and that the sheet has durability that does not cause poor appearance such as lifting or peeling at the adhesive interface with the adhesive layer even in high temperature or high temperature / high humidity environments. Another issue is that PP resin is a low polarity material and therefore difficult to adhere to. Furthermore, the importance of high transparency is increasing from the viewpoint of design, and there is a demand for an adhesive composition for decorative sheets that can satisfy each of these performances in a well-balanced manner.
[0010] As a result of investigations by the inventors, the pressure-sensitive adhesive compositions described in Patent Documents 1 and 2 did not exhibit satisfactory performance when used with PP resin, which is a low-polarity adherend.
[0011] In other words, no pressure-sensitive adhesive composition for decorative sheets has been developed to date that can conform to complex shapes having unevenness in the decoration of molded articles, and can impart excellent adhesion to low-polarity adherends, transparency, and appearance to molded articles. [Means for solving the problem]
[0012] The present inventors conducted extensive research to solve the above problems and arrived at the present invention. That is, the adhesive composition for decorative sheets contains a (meth)acrylic acid ester copolymer (A), a curing agent (B), and a tackifier resin (C) having a softening point of less than 130°C, and contains 2 parts by mass or more and 60 parts by mass or less of the tackifier resin (C) per 100 parts by mass of the (meth)acrylic acid ester copolymer (A). Effect of the Invention
[0013] The present invention makes it possible to provide a pressure-sensitive adhesive composition for decorative sheets, decorative sheets, decorative structures, and methods for producing the same, which can conform to complex shapes having unevenness in the decoration of molded articles, and can impart excellent adhesion to low-polarity adherends, transparency, and appearance to molded articles. It has been discovered that when an adhesive layer is formed from an adhesive composition containing a specified (meth)acrylic acid ester copolymer (A), a curing agent (B), and a tackifier resin (C), it is possible to decorate a molded article by conforming to a complex shape having uneven portions, and to impart excellent adhesion to low-polarity substrates, transparency, and an excellent appearance to the molded article. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The pressure-sensitive adhesive composition for decorative sheets, the decorative sheet, the decorative structure, and the method for producing a decorative structure according to the present invention have the following configurations [1] to [7].
[0015] [1] A pressure-sensitive adhesive composition for decorative sheets, comprising: a (meth)acrylic acid ester copolymer (A), a curing agent (B), and a tackifier resin (C) having a softening point of less than 130°C, wherein the (meth)acrylic acid ester copolymer (A) is a copolymer of a monomer mixture, and the tackifier resin (C) is present in an amount of 2 parts by weight or more and 60 parts by weight or less per 100 parts by weight of the (meth)acrylic acid ester copolymer (A).
[0016] [2] The pressure-sensitive adhesive composition for decorative sheets according to [1], characterized in that the monomer mixture contains two or more kinds selected from the group consisting of the following (a1), (a2), and (a3), and the total content of (a1), (a2), and (a3) is 75 mass% or more in 100 mass% of the monomer mixture: (a1): (meth)acrylic acid alkyl ester monomer having an alkyl carbon number of 4 to 8 and a homopolymer glass transition temperature of 0° C. or less (a2): (meth)acrylic acid alkyl ester monomer having 1 to 3 alkyl carbon atoms (a3): Vinyl ester monomer of a carboxylic acid having an alkyl group having 1 to 3 carbon atoms
[0017] [3] The pressure-sensitive adhesive composition for decorative sheets according to [1], wherein the tackifier resin (C) is at least one selected from the group consisting of terpene resins and synthetic hydrocarbon resins.
[0018] [4] The pressure-sensitive adhesive composition for decorative sheets according to [1], which is used for attachment to an adherend by vacuum forming or vacuum / pressure forming.
[0019] [5] A decorative sheet comprising a substrate and an adhesive layer made of the adhesive composition for decorative sheets according to any one of [1] to [4].
[0020] [6] A decorative structure comprising an adherend and the decorative sheet according to [5].
[0021] [7] A method for producing a decorative structure, comprising forming the decorative structure according to [6], in which the decorative sheet is integrated with an adherend by vacuum forming or vacuum-pressure forming.
[0022] The present invention will be described in detail below. However, it goes without saying that other embodiments are also included in the scope of the present invention as long as they conform to the spirit of the present invention.
[0023] In the present invention, the term "sheet" refers to a flexible laminate, and includes a thin laminate called a "film."
[0024] In the present invention, "(meth)acrylic" means either one or both of "acrylic" and "methacrylic", and "(meth)acrylate" means either one or both of "acrylate" and "methacrylate".
[0025] In the present invention, a numerical range specified using "to" includes the numerical values before and after "to" as the lower and upper limit values.
[0026] In this specification, "Mw" is the weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC), and "Mn" is the number average molecular weight in terms of polystyrene measured by GPC. The weight average molecular weight and number average molecular weight can be measured by the method described in the section [Examples].
[0027] In addition, the following describes in detail the embodiments of the present invention, but the following description is an example (representative example) of an embodiment of the present invention, and the present invention is not limited to these contents as long as it does not deviate from the gist of the present invention.
[0028] <Adhesive composition> The adhesive composition comprises a (meth)acrylic acid ester copolymer (A), a curing agent (B) and a tackifier resin (C) having a softening point of less than 130°C, and is characterized in that it contains 2 to 60 parts by mass of the tackifier resin (C) per 100 parts by mass of the (meth)acrylic acid ester copolymer (A).
[0029] <(Meth)acrylic acid ester copolymer (A)> The (meth)acrylic acid ester copolymer (A) (hereinafter also referred to as copolymer (A)) contained in the present pressure-sensitive adhesive composition is a copolymer obtained by polymerizing all or part of a mixture of monomers containing a (meth)acrylic acid alkyl ester, and a monomer having a functional group or other monomers is used as necessary.
[0030] The (meth)acrylic acid ester copolymer (A) is preferably a copolymer of a monomer mixture containing two or more selected from the group consisting of the following (a1), (a2), and (a3). The total content of (a1), (a2), and (a3) is preferably 75% by mass or more and less than 100% by mass, more preferably 82% by mass or more, and particularly preferably 90% by mass or more, based on 100% by mass of the monomer mixture. By being in the above range, adhesion to low-polarity adherends and unevenness-following ability can be ensured. (a1): A (meth)acrylic acid alkyl ester monomer having a homopolymer glass transition temperature of 0° C. or lower and an alkyl group having 4 to 8 carbon atoms. (a2): (meth)acrylic acid alkyl ester monomer having an alkyl group with 1 to 3 carbon atoms (a3): Vinyl ester monomer of a carboxylic acid having an alkyl group having 1 to 3 carbon atoms
[0031] The monomer mixture constituting the (meth)acrylic acid ester copolymer (A) more preferably contains (a1), which makes it possible to achieve both high levels of adhesive strength and durability.
[0032] In the present invention, the glass transition temperature (Tg) of the copolymer (A) is a value calculated based on the following formula (1) (Fox formula). 1 / Tg=W1 / Tg1+W2 / Tg2+ +Wn / Tgn (Formula 1) [In formula (1), Tg is the Tg (unit: K) of the acrylic polymer (A), Tgi (i = 1, 2, ... n) is the Tg (unit: K) when the radical polymerizable monomer i forms a homopolymer, and Wi (i = 1, 2, ... n) is the mass fraction of the radical polymerizable monomer i in all monomer components. For the Tg of the homopolymer, published values such as literature values and catalog values are used.] The above formula (1) is a calculation formula when the copolymer (A) is composed of n types of monomer components, namely, monomer 1, monomer 2, . . . , monomer n.
[0033] The (meth)acrylic acid alkyl ester monomer (a1) having a homopolymer glass transition temperature of 0° C. or less and an alkyl group having 4 to 8 carbon atoms is not particularly limited, but specific examples include butyl acrylate (Tg: −54° C.), isobutyl acrylate (Tg: −24° C.), 2-ethylhexyl acrylate (Tg: −70° C.), n-octyl acrylate (Tg: −65° C.), etc. In terms of compatibility with the tackifier resin, butyl acrylate and 2-ethylhexyl acrylate are preferred, and it is particularly preferred that the ratio of 2-ethylhexyl acrylate is 40% by mass or more in the total of 100% by mass of (a1), (a2) and (a3).
[0034] Examples of the (meth)acrylic acid alkyl ester monomer (a2) having an alkyl carbon number of 1 to 3 include methyl (meth)acrylate, ethyl (meth)acrylate, and propyl (meth)acrylate, and from the viewpoint of durability after molding, methyl (meth)acrylate and ethyl acrylate are preferred.
[0035] Examples of the vinyl ester monomer (a3) of a carboxylic acid having an alkyl group having 1 to 3 carbon atoms include vinyl acetate, vinyl propionate, and vinyl butyrate, with vinyl acetate being preferred from the viewpoint of adhesive strength.
[0036] The monomer mixture constituting the copolymer (A) preferably further contains a monomer having a functional group that forms a crosslinked structure with the curing agent (B). Examples of the functional group include a hydroxyl group, an acidic group, an unsaturated double bond group, and an epoxy group. These may be used alone or in combination of two or more kinds. In the present pressure-sensitive adhesive composition, from the viewpoints of adhesion to substrates and durability after molding, it is particularly preferable that the monomer mixture constituting copolymer (A) contains a hydroxyl group-containing monomer and / or an acidic group-containing monomer, and it is even more preferable that it contains an acidic group-containing monomer.
[0037] Examples of the acidic group-containing monomer include (meth)acrylic acid, 2-carboxyethyl acrylate, itaconic acid, maleic acid, styrenesulfonic acid, 2-(meth)acryloyloxyethyl-succinic acid, 2-(meth)acryloyloxyethyl-phthalic acid, and 2-acryloyloxyethylhexahydrophthalic acid. These may be used alone or in combination of two or more. Among them, (meth)acrylic acid and 2-carboxyethyl acrylate are preferred from the viewpoint of polymerizability.
[0038] The content of the acidic group-containing monomer in 100% by mass of the monomer mixture constituting the copolymer (A) is not particularly limited, but is preferably 0.1% by mass or more and 10% by mass or less from the viewpoint of compatibility with the tackifier resin.
[0039] Examples of hydroxyl group-containing monomers include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, and polyalkylene glycol mono(meth)acrylate-based monomers having a hydroxyl group, as well as allyl ether monomers having a hydroxyl group, such as polyalkylene glycol allyl ether. From the viewpoint of copolymerizability and reactivity with the curing agent (B), 2-hydroxyethyl (meth)acrylate or 4-hydroxybutyl (meth)acrylate is preferred.
[0040] The content of the hydroxyl group-containing monomer in 100% by mass of the monomer mixture constituting the copolymer (A) is preferably from 0.01 to 10% by mass from the viewpoint of durability after molding.
[0041] Further, examples of other monomers that can be contained in the monomer mixture constituting the copolymer (A) include the following.
[0042] (Meth)acrylic acid alkyl ester monomers having an alkyl group having 9 to 26 carbon atoms, such as nonyl acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, behenyl (meth)acrylate, eicosanyl (meth)acrylate, and hexacosanyl (meth)acrylate. (meth)acrylic acid ester monomers having an aliphatic ring, such as cyclohexyl (meth)acrylate, 4-t-butylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and 3,3,5-trimethylcyclohexyl (meth)acrylate; (meth)acrylic acid ester monomers having an aromatic ring, such as benzyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, 2-(o-phenylphenoxy)ethyl (meth)acrylate, and nonylphenoxy polyethylene glycol (meth)acrylate; (meth)acrylic acid ester monomers having an alkoxy group, such as 2-methoxymethyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxymethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate; (meth)acrylic acid ester monomers having a polyether chain, such as methoxypolyethylene glycol (meth)acrylate, ethoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, ethoxypolypropylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, and phenoxypolypropylene glycol (meth)acrylate; N-vinyl cyclic amide monomers such as N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, and N-vinyl-3,5-morpholinedione; (meth)acrylamide-based monomers such as (meth)acrylamide, N-alkyl(meth)acrylamide, N,N-dialkyl(meth)acrylamide, N-hydroxyalkyl(meth)acrylamide, and N-alkoxyalkyl(meth)acrylamide; N,N-dialkyl(meth)acrylamide monomers such as N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, N,N-di(n-butyl)(meth)acrylamide, and N,N-di(t-butyl)(meth)acrylamide; N-hydroxyalkyl (meth)acrylamide monomers such as N-methylol (meth)acrylamide, N-(2)-hydroxyethyl) (meth)acrylamide, N-(2-hydroxypropyl) (meth)acrylamide, N-(1-hydroxypropyl) (meth)acrylamide, N-(3-hydroxypropyl) (meth)acrylamide, N-(2-hydroxybutyl) (meth)acrylamide, N-(3-hydroxybutyl) (meth)acrylamide, N-(4-hydroxybutyl) (meth)acrylamide, and N-methyl-N-2-hydroxyethyl (meth)acrylamide; N-alkoxyalkyl(meth)acrylamides such as N-methoxymethyl(meth)acrylamide and N-butoxymethyl(meth)acrylamide; Monomers having an acidic group other than a carboxy group, such as 2-(meth)acryloyloxyethyl acid phosphate and 2-methacryloyloxyethyl acid phosphate; These may or may not be contained in the monomer mixture constituting the copolymer (A) as required.
[0043] The content of other monomers in 100% by mass of the monomer mixture constituting the copolymer (A) is not particularly limited, but from the viewpoint of adhesive strength, it is preferably from 0% by mass to 25% by mass.
[0044] The polymerization form of the (meth)acrylic acid ester copolymer (A) is not particularly limited. That is, the copolymer (A) may be any of an alternating copolymer, a random copolymer, a block copolymer, and a graft copolymer of each monomer including a (meth)acrylic acid alkyl ester. For example, the block copolymer may be a diblock or a triblock.
[0045] The copolymer (A) can be synthesized by a conventionally known method, for example, by a known polymerization method such as a solution polymerization method, a bulk polymerization method, an emulsion polymerization method, or a suspension polymerization method. The copolymer (A) can be synthesized by a known polymerization method such as a living radical polymerization method or an active energy ray polymerization method. In this case, the monomer mixture for synthesizing the copolymer (A) can contain a photopolymerization initiator or a conventionally known additive. As the active energy ray, ultraviolet light, visible light, X-rays, gamma rays, or electron beams can be used. In addition, light sources such as a low pressure mercury lamp, a medium pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a xenon lamp, a metal halide lamp, an electrodeless lamp, and an LED can be used for irradiation with ultraviolet light.
[0046] The blending ratio of each structural unit (monomer component) of the copolymer (A) can be determined using various instruments such as nuclear magnetic resonance analysis (NMR) and gas chromatography (GC).
[0047] The weight average molecular weight (Mw) of the (meth)acrylic acid ester copolymer (A) is preferably more than 300,000, more preferably 500,000 or more, and even more preferably 600,000 or more. The weight average molecular weight of the copolymer (A) is preferably 1,500,000 or less, more preferably 1,300,000 or less, and even more preferably 1,200,000 or less. When the Mw of the copolymer (A) satisfies the above-mentioned lower limit condition, it is easy to ensure a viscosity suitable for coating, and it is also easy to prevent the decorative sheet portion from shifting after decoration of the molded article, which would cause deterioration in the appearance of the decorated molded article.
[0048] <Hardening agent (B)> The pressure-sensitive adhesive composition contains a curing agent (B). By introducing a crosslinking group into the (meth)acrylic acid ester copolymer (A) and crosslinking it with the curing agent (B), the cohesive strength, adhesive strength, and durability after molding of the pressure-sensitive adhesive layer can be improved.
[0049] Examples of the curing agent (B) include isocyanate-based curing agents, epoxy-based curing agents, aziridine-based curing agents, metal chelate-based curing agents, amine-based curing agents, and acrylate-based curing agents. Among these, isocyanate-based curing agents, epoxy-based curing agents, and metal chelate-based curing agents are preferred, and epoxy-based curing agents and metal chelate-based curing agents are more preferred from the viewpoint of repositionability, and epoxy-based curing agents are particularly preferred from the viewpoint of durability in high-temperature environments. It is preferable to use one type of curing agent alone.
[0050] Examples of the isocyanate-based curing agent include adducts of diisocyanates such as tolylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, tetramethylxylylene diisocyanate, naphthalene diisocyanate, triphenylmethane triisocyanate, and polymethylene polyphenyl isocyanate with polyol compounds such as trimethylolpropane, as well as biuret forms and isocyanurates thereof, as well as adducts of the above diisocyanates with polyether polyols, polyester polyols, acrylic polyols, polybutadiene polyols, and the like. Compounds having three or more isocyanate groups in the molecule, such as adducts with any of polyols such as ene polyols and polyisoprene polyols; compounds having two isocyanate groups in the molecule, such as diisocyanates such as tolylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, tetramethyl xylylene diisocyanate, naphthalene diisocyanate, triphenylmethane triisocyanate, and polymethylene polyphenyl isocyanate, and allophanate compounds of hexamethylene diisocyanate; and the like. Among these, trimethylolpropane adducts of tolylene diisocyanate are preferred because they can easily adjust the adhesive properties. The number of isocyanate groups is the average number.
[0051] Examples of epoxy curing agents include bisphenol A-epichlorohydrin type epoxy resins, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, diglycidylaniline, N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraglycidylaminophenylmethane. From the viewpoint of curability and durability, N,N,N',N'-tetraglycidyl-m-xylylenediamine and 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane are particularly preferred.
[0052] Examples of the aziridine-based curing agent include β-aziridinyl propionate, trimethylolpropane tris(β-aziridinyl propionate), etc. In addition, examples of commercially available products include “TAZO” and “TAZM” manufactured by Sogo Pharmaceutical Co., Ltd., and “ChemiTite PZ-33” manufactured by Nippon Shokubai Co., Ltd.
[0053] Examples of the metal chelate curing agent include coordination compounds of polyvalent metals such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium and zirconium with acetylacetone or ethyl acetoacetate.
[0054] Examples of the amine-based curing agent include hexamethylenediamine, triethyldiamine, polyethyleneimine, hexamethylenetetramine, diethylenetriamine, triethyltetramine, isophoronediamine, amino resins, and methylene resins.
[0055] Examples of the acrylate-based curing agent include polyfunctional acrylates such as 1,6-hexanediol acrylate.
[0056] The content of the curing agent (B) may be appropriately changed depending on the desired physical properties such as the type and degree of crosslinking of the copolymer (A), but from the viewpoints of adhesive strength, repositionability, and durability at high temperatures, it is preferably 0.01 to 3 parts by mass, more preferably 0.015 to 1 part by mass, even more preferably 0.018 to 0.5 parts by mass or less, and particularly preferably 0.02 to 0.06 parts by mass, relative to 100 parts by mass of the copolymer (A). In particular, by setting the content of the epoxy compound as the curing agent within the above range, it is possible to achieve a high degree of both adhesion and heat resistance in a high-temperature environment.
[0057] The degree of crosslinking of the present pressure-sensitive adhesive composition is indicated by the gel fraction, and the method for measuring it is as shown in the Examples. Since the higher the gel fraction, the better the repositionability and durability after molding, the gel fraction after crosslinking of the pressure-sensitive adhesive composition of the present invention is preferably 50% or more. The gel fraction may be 100%. The degree of crosslinking of the pressure-sensitive adhesive composition can be appropriately adjusted by changing the blending amount of the curing agent (B), etc.
[0058] <Tackifying resin (C)> The adhesive composition of the present invention contains a tackifier resin (tackifier) (C) having a softening point of less than 130° C. The softening point of the tackifier resin (C) is preferably less than 110° C., more preferably 99° C. or less. The softening point is preferably 25° C. or more, more preferably 75° C. or more. By setting the softening point within the above range, it is possible to achieve a high degree of compatibility between the appearance of the coating film and adhesive performance.
[0059] The content of the tackifier resin (C) is from 2 to 60 parts by mass, preferably from 7 to 40 parts by mass, and more preferably from more than 10 to less than 30 parts by mass, relative to 100 parts by mass of the (meth)acrylic acid ester copolymer (A). By setting the content within the above range, it is possible to achieve a high degree of compatibility between the appearance and adhesive performance of the coating film.
[0060] The softening point of the tackifier resin (C) is determined by the ring and ball method (JIS K 5902) or by a published value such as a literature value or catalog value. If the published value is set for a temperature range, the average value of the lower and upper limits is used.
[0061] The tackifier resin (C) is not particularly limited, but examples thereof include rosin-based resins, terpene-based resins, synthetic hydrocarbon-based resins, and the like.
[0062] Examples of rosin-based resins include rosin ester, polymerized rosin, hydrogenated rosin, disproportionated rosin, maleic acid modified rosin, fumaric acid modified rosin, rosin phenolic resin, and natural rosin.
[0063] Examples of terpene resins include α-pinene resins, β-pinene resins, dipentene resins, aromatic modified terpene resins, hydrogenated terpene resins, terpene phenol resins, acid modified terpene resins, styrenated terpene resins, and styrene-aliphatic hydrocarbon copolymer resins.
[0064] Examples of synthetic hydrocarbon resins include aliphatic petroleum resins, aromatic petroleum resins, aliphatic / aromatic petroleum resins, hydrogenated petroleum resins, coumarone-indene resins, and phenol resins. From the viewpoint of adhesive strength and compatibility, aliphatic petroleum resins, aromatic petroleum resins, aliphatic / aromatic petroleum resins and hydrogenated petroleum resins are preferred, with hydrogenated petroleum resins being particularly preferred.
[0065] From the viewpoint of obtaining good adhesion to the object to be affixed, it is preferable to use a rosin-based resin, a terpene-based resin, or a synthetic hydrocarbon resin as the tackifier resin (C), and from the viewpoint of transparency, it is more preferable to use at least one of a terpene-based resin and a synthetic hydrocarbon resin. It is particularly preferable to use a synthetic hydrocarbon resin. The tackifier resin may be used alone or in combination of two or more kinds.
[0066] In addition to the copolymer (A), the curing agent (B) and the tackifier resin (C), the pressure-sensitive adhesive composition may contain, as necessary, any additives such as a solvent, a resin other than the copolymer (A), a plasticizer, a silane coupling agent, a leveling agent, inorganic and / or organic fine particles, an ultraviolet absorber, a light stabilizer, an antioxidant, etc. The amount of these additives added can be appropriately selected within a range in which the effects of the present invention can be obtained, and for example, it is preferable to appropriately set the content of the copolymer (A) within the above range.
[0067] Resins other than the (meth)acrylic acid ester copolymer (A) include known thermoplastic resins, such as low-density polyethylene, very low-density polyethylene, low-crystalline (amorphous) polypropylene, ionomer resins, ethylene copolymers such as ethylene-vinyl acetate copolymers, ethylene-(meth)acrylic acid copolymers, ethylene-(meth)acrylic acid ester-maleic anhydride copolymers, and ethylene-glycidyl methacrylate copolymers, as well as olefin-based copolymers such as polyolefin-modified polymers, as well as thermoplastic elastomers such as butadiene-based elastomers, ester-based elastomers, styrene-based elastomers, styrene-butadiene-based elastomers, styrene-isoprene-based elastomers, and polyurethane-based elastomers, as well as thermoplastic polyesters, as well as polyamide-based resins such as polyamide-based copolymers, polyurethanes, polystyrene-based resins, cellophane, polyacrylonitrile, and polyvinyl chloride-based resins such as vinyl chloride-vinyl acetate copolymers, etc. These resins may be used alone or in combination of two or more. The content of these other resins is preferably less than 10 mass% based on 100 mass% of the solid content of the pressure-sensitive adhesive composition, whereby good compatibility is easily obtained and appropriate adhesive strength can be easily obtained.
[0068] When applying the present pressure-sensitive adhesive composition to an object to be affixed, the solvent used in the polymerization of the (meth)acrylic acid ester copolymer (A) may be used as is, or further solvent may be added, and any suitable solvent may be used.
[0069] Examples of the solvent include methyl acetate, ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, xylene, hexane, acetone, methyl ethyl ketone, methyl isobutyl ketone, methanol, ethanol, n-propanol, and isopropanol. These organic solvents may be used alone or in combination of two or more. The viscosity of the adhesive composition can be adjusted by adding these organic solvents, or the viscosity can be reduced by heating the adhesive composition. From the viewpoint of solubility and drying property, it is preferable to use a solvent having an SP value of 9 or more. Examples of organic solvents having an SP value of 9 or more include ethyl acetate, butyl acetate, methyl ethyl ketone, isopropanol, etc. Among these, it is preferable to use ethyl acetate. On the other hand, from the viewpoint of decreasing the viscosity of the pressure-sensitive adhesive composition, it is preferable to use a solvent having an SP value of less than 9. Examples of organic solvents having an SP value of less than 9 include hexane, heptane, and octane.
[0070] <Decorative sheet> The present adhesive composition described above can be preferably used for a decorative sheet. The decorative sheet according to the present invention (hereinafter also referred to as the present decorative sheet) comprises a substrate and an adhesive layer made of a cured product of the present adhesive composition. If necessary, the exposed surface of the adhesive layer can be covered with a release sheet. The release sheet is peeled off when the adhesive sheet is attached to an adherend. The substrate is not particularly limited, and examples thereof include resin sheets, paper, and metal foils. The substrate may be a laminated sheet in which any one or more layers are laminated on at least one surface of the substrate. The surface of the substrate on which any adhesive layer is formed may be subjected to an easy-adhesion treatment such as corona discharge treatment and application of an anchor coating agent, if necessary. The release sheet is not particularly limited, and any known release sheet can be used, which is obtained by subjecting the surface of a base sheet such as a resin sheet or paper to a known release treatment such as coating with a release agent.
[0071] The method for producing the present decorative sheet having an adhesive layer can be appropriately used by a conventionally known method, and is not particularly limited. For example, the present composition, which is diluted with a solvent as necessary, is coated on a sheet on which a surface layer and a decorative layer are formed by knife coating, bar coating, blade coating, doctor coating, roll coating, cast coating, etc. to form a coating film. Then, the adhesive layer (solidified material) can be formed on the sheet by heating and drying or curing as necessary. In addition, when the copolymer (A) contained in the present composition needs to be crosslinked by active energy rays, the present composition is applied onto a sheet, and then the sheet is irradiated with active energy rays to form a pressure-sensitive adhesive layer (crosslinked product). In this case, for example, a belt conveyor type ultraviolet ray irradiation device is used to irradiate the pressure-sensitive adhesive composition applied onto the sheet with ultraviolet rays to obtain a pressure-sensitive adhesive layer. The ultraviolet ray irradiation dose is, for example, 500 mJ / cm. 2 More than 5000mJ / cm 2 It can be as follows: This decorative sheet has a moderate adhesive strength at room temperature (e.g., 25°C), has excellent adhesiveness when bonded at high temperatures (e.g., 100 to 130°C), and can maintain its properties for a long period of time at high temperatures (e.g., 100°C for 7 days). Therefore, this decorative sheet can be applied to the decoration of aircraft, automobiles, interior and exterior of building materials, nursing and medical fields, electrical appliances, electronic parts, smartphones, furniture, musical instruments, Shinkansen window frame walls, etc., by three-dimensional surface decoration (Three Dimension Overlay Method: TOM molding), which is a type of vacuum and compressed air molding.
[0072] <Decorative structure and method for producing same> The decorative structure according to the present invention (hereinafter also referred to as the present structure) can be formed by attaching a decorative sheet to an adherend using the present pressure-sensitive adhesive composition. The adherend is not particularly limited, and various shapes of objects (e.g., molded products having three-dimensional shapes) can be used. The decorative sheet using the present pressure-sensitive adhesive composition is used for attachment to an adherend by a vacuum forming method and a vacuum-pressure forming method. Conventionally known methods can be appropriately applied for the vacuum forming method and the vacuum-pressure forming method.
[0073] More specifically, the present decorated structure can include, for example, a surface layer, a decorative layer, and a pressure-sensitive adhesive layer in this order. The surface layer is a layer that becomes the surface of the decorated molded product, and any layer that is conventionally known in the field of decorative sheets can be used as appropriate. The surface layer can be made of various resins, such as acrylic resin, polyurethane, fluororesin, and polyvinyl chloride. The exposed surface of the surface layer may also be embossed. The decorative layer is for decorating the object to be decorated, and various materials can be used depending on the intended use. The decorative layer can contain at least one resin selected from the group consisting of olefin resins, styrene resins, and vinyl chloride resins. The decorative layer may further contain other layers such as a design layer, a bulk layer, and a bonding layer as optional elements. The number of layers of the decorative sheet, the type, arrangement, thickness, etc. of each layer can be appropriately selected and are not particularly limited. The adhesive layer is a layer for attaching a decorative sheet to an adherend (e.g., a molded product formed into a three-dimensional shape), and can be formed by drying the adhesive composition (e.g., after applying it to a substrate) or by crosslinking it by irradiating it with ultraviolet light, etc. EXAMPLES
[0074] Next, the present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples. In the examples, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass". In addition, the blending amounts in the tables are parts by mass.
[0075] <Measurement of weight average molecular weight (Mw)> The Mw of the (meth)acrylic acid ester copolymer (A) was measured by the following method. The copolymer (A) dissolved in tetrahydrofuran (THF) was subjected to liquid chromatography (gel permeation chromatography) which separates and quantifies based on the difference in molecular size, and the Mw was identified. The measurement device used was a Shimadzu Corporation GPC LC-GPC system "Prominence" (product name). The weight average molecular weight was determined in terms of polystyrene. Four columns (product name: GMHXL, manufactured by Tosoh Corporation) and one (product name: HXL-H, manufactured by Tosoh Corporation) were connected in series, and the measurement was performed at a flow rate of 1.0 ml / min and a column temperature of 40°C.
[0076] [Production Example of (Meth)Acrylic Acid Ester Copolymer (A)] <Synthesis Example 1> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 45 parts of 2-ethylhexyl acrylate, 3.5 parts of ethyl acrylate, 1.5 parts of acrylic acid, 60 parts of acetone, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 45 parts of 2-ethylhexyl acrylate, 3.5 parts of ethyl acrylate, 1.5 parts of acrylic acid, 20 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and after starting the reaction, the contents of the dropping funnel were dropped over 1.5 hours, while the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 40%. The weight average molecular weight (Mw) of the acrylic polymer was 980,000.
[0077] <Synthesis Example 2> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 36 parts of butyl acrylate, 5 parts of 2-ethylhexyl acrylate, 7.5 parts of ethyl acrylate, 1.5 parts of acrylic acid, 60 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 36 parts of butyl acrylate, 5 parts of 2-ethylhexyl acrylate, 7.5 parts of ethyl acrylate, 1.5 parts of acrylic acid, 30 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and after starting the reaction, the contents of the dropping funnel were added dropwise over 1.5 hours, and a polymerization reaction was carried out for 5 hours at reflux temperature under a nitrogen atmosphere. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 40%. The weight average molecular weight (Mw) of the acrylic polymer was 980,000.
[0078] <Synthesis Example 3> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 10 parts of butyl acrylate, 36 parts of 2-ethylhexyl acrylate, 2 parts of ethyl acrylate, 2 parts of acrylic acid, 40 parts of acetone, 20 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 10 parts of butyl acrylate, 36 parts of 2-ethylhexyl acrylate, 2 parts of ethyl acrylate, 2 parts of acrylic acid, 20 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and the reaction was started. The contents of the dropping funnel were added dropwise over 1.5 hours, and the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 40%. The weight average molecular weight (Mw) of the acrylic polymer was 970,000.
[0079] <Synthesis Example 4> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 5 parts of butyl acrylate, 29 parts of 2-ethylhexyl acrylate, 14 parts of ethyl acrylate, 2 parts of acrylic acid, 60 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 5 parts of butyl acrylate, 29 parts of 2-ethylhexyl acrylate, 14 parts of ethyl acrylate, 2 parts of acrylic acid, 20 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and after starting the reaction, the contents of the dropping funnel were dropped over 1.5 hours, while the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 40%. The weight average molecular weight (Mw) of the acrylic polymer was 960,000.
[0080] <Synthesis Example 5> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 28 parts of 2-ethylhexyl acrylate, 20 parts of ethyl acrylate, 2 parts of acrylic acid, 60 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 28 parts of 2-ethylhexyl acrylate, 20 parts of ethyl acrylate, 2 parts of acrylic acid, 20 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and the reaction was started. The contents of the dropping funnel were added dropwise over 1.5 hours, while the polymerization reaction was carried out for 5 hours at reflux temperature under a nitrogen atmosphere. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 40%. The weight average molecular weight (Mw) of the acrylic polymer was 970,000.
[0081] <Synthesis Example 6> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 23 parts of 2-ethylhexyl acrylate, 25 parts of ethyl acrylate, 2 parts of acrylic acid, 60 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 23 parts of 2-ethylhexyl acrylate, 25 parts of ethyl acrylate, 2 parts of acrylic acid, 30 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and the reaction was started. The contents of the dropping funnel were added dropwise over 1.5 hours, and the polymerization reaction was carried out for 5 hours at reflux temperature under a nitrogen atmosphere. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 40%. The weight average molecular weight (Mw) of the acrylic polymer was 980,000.
[0082] <Synthesis Example 7> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 44.5 parts of 2-ethylhexyl acrylate, 3.5 parts of methyl methacrylate, 2 parts of acrylic acid, 60 parts of acetone, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 44.5 parts of 2-ethylhexyl acrylate, 3.5 parts of methyl methacrylate, 2 parts of acrylic acid, 20 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and after the reaction was started, the contents of the dropping funnel were dropped over 1.5 hours, while the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 40%. The weight average molecular weight (Mw) of the acrylic polymer was 960,000.
[0083] <Synthesis Example 8> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 10 parts of butyl acrylate, 36 parts of 2-ethylhexyl acrylate, 2 parts of vinyl acetate, 2 parts of acrylic acid, 40 parts of acetone, 20 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 10 parts of butyl acrylate, 36 parts of 2-ethylhexyl acrylate, 2 parts of vinyl acetate, 2 parts of acrylic acid, 20 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and the reaction was started. The contents of the dropping funnel were added dropwise over 1.5 hours, and the polymerization reaction was carried out for 5 hours at reflux temperature under a nitrogen atmosphere. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 40%. The weight average molecular weight (Mw) of the acrylic polymer was 960,000.
[0084] <Synthesis Example 9> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 26.5 parts of butyl acrylate, 7.5 parts of butyl methacrylate, 14 parts of ethyl acrylate, 2 parts of acrylic acid, 60 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 26.5 parts of butyl acrylate, 7.5 parts of butyl methacrylate, 14 parts of ethyl acrylate, 2 parts of acrylic acid, 40 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and the reaction was started. The contents of the dropping funnel were added dropwise over 1.5 hours, and the polymerization reaction was carried out for 5 hours at reflux temperature under a nitrogen atmosphere. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 40%. The weight average molecular weight (Mw) of the acrylic polymer was 830,000.
[0085] <Synthesis Example 10> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 24 parts of butyl acrylate, 10 parts of butyl methacrylate, 14 parts of ethyl acrylate, 2 parts of acrylic acid, 60 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 24 parts of butyl acrylate, 10 parts of butyl methacrylate, 14 parts of ethyl acrylate, 2 parts of acrylic acid, 30 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and the reaction was started. The contents of the dropping funnel were added dropwise over 1.5 hours, and the polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 40%. The weight average molecular weight (Mw) of the acrylic polymer was 740,000.
[0086] <Synthesis Example 11> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 18.5 parts of 2-ethylhexyl acrylate, 30 parts of ethyl acrylate, 1.5 parts of acrylic acid, 60 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 18.5 parts of 2-ethylhexyl acrylate, 30 parts of ethyl acrylate, 1.5 parts of acrylic acid, 40 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere, and after the reaction was started, the contents of the dropping funnel were dropped over 1.5 hours, and a polymerization reaction was carried out for 5 hours at reflux temperature under a nitrogen atmosphere. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 40%. The weight average molecular weight (Mw) of the acrylic polymer was 960,000.
[0087] <Synthesis Example 12> A reaction vessel (hereinafter sometimes simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was charged with 33 parts of butyl acrylate, 15 parts of butyl methacrylate, 2 parts of acrylic acid, 60 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN), and the air in the reaction vessel was then replaced with nitrogen gas. Furthermore, 33 parts of butyl acrylate, 15 parts of butyl methacrylate, 2 parts of acrylic acid, 20 parts of ethyl acetate, and 0.01 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into the dropping funnel. Next, the reaction vessel was heated to 80°C while stirring under a nitrogen atmosphere to start the reaction, and the contents of the dropping funnel were added dropwise over 1.5 hours, while performing a polymerization reaction at reflux temperature under a nitrogen atmosphere for 5 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution with a non-volatile content of 40%. The weight average molecular weight (Mw) of the acrylic polymer was 700,000.
[0088] [Table 1]
[0089] The abbreviations in Table 1 are listed below. 2EHA: 2-ethylhexyl acrylate BA: Butyl acrylate MMA: Methyl methacrylate EA: Ethyl acrylate VAc: Vinyl acetate BMA: Butyl methacrylate AA: Acrylic acid
[0090] Example 1 100 parts of the copolymer (Synthesis Example 1) obtained in the above-mentioned Production Example was mixed with 0.05 parts (non-volatile content) of TETRAD-X (manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a curing agent (B), and further mixed with 8 parts (non-volatile content) of Alcon P-90 adjusted to 50% non-volatile content with toluene as a tackifier resin solvent (C), and 4 parts (non-volatile content) of Petcol LX similarly adjusted to 50% non-volatile content were mixed, and ethyl acetate was added to adjust the non-volatile content to 25%, to obtain a pressure-sensitive adhesive composition of Example 1. The obtained pressure-sensitive adhesive composition was evaluated according to the measurement method and evaluation method shown below.
[0091] (Examples 2 to 26, Comparative Examples 1 to 3) A pressure-sensitive adhesive composition was obtained in the same manner as in Example 1, except that the copolymer (A), the curing agent (B), and the tackifier resin (C) were changed to those shown in Table 2. The pressure-sensitive adhesive composition obtained was evaluated according to the measurement and evaluation methods shown below.
[0092] <How to make decorative sheets> The obtained adhesive composition was applied to the release-treated surface of a polyethylene terephthalate (PET) film (thickness 38 μm) with one side subjected to release treatment so that the thickness after drying would be 25 μm. Then, after drying at 105° C. for 2 minutes, the coating film was laminated to a commercially available polyvinyl chloride film and aged for 7 days in an atmosphere of 23° C. and relative humidity 50% (hereinafter referred to as 50% RH) to prepare a decorative sheet.
[0093] (SUS adhesion) After curing for 5 hours under an atmosphere of 23°C-50% RH, a test piece 25 mm wide and 150 mm long was cut out from the decorative sheet. The release sheet was peeled off from the cut decorative sheet, and the exposed adhesive layer was attached to the surface of a stainless steel plate (SUS304) and pressed with a 2 kg roll once. The sheet was then left for 24 hours under an atmosphere of 23°C-50% RH. Next, the adhesive strength (adhesive strength before heating) was measured using a tensile tester (Tensilon: manufactured by Orientec Co., Ltd.) in accordance with JIS Z0237, at a peel speed of 300 mm / min and a peel angle of 180°. The evaluation criteria are as follows. [Evaluation Criteria] ◎: 13N / 25mm or more, excellent. ○: 8N / 25mm or more but less than 13N / 25mm, good. △: 1N / 25mm or more but less than 8N / 25mm, usable. ×: Less than 1N / 25mm, not practical.
[0094] (PP adhesive strength) After curing for 5 hours under an atmosphere of 23°C-50% RH, a test piece with a width of 25 mm and a length of 150 mm was cut out from the decorative sheet. The release sheet was peeled off from the cut decorative sheet, and the exposed adhesive layer was attached to the surface of a polypropylene plate and pressed with a 2 kg roll once. The sheet was then left for 24 hours under an atmosphere of 23°C-50% RH. Next, the adhesive strength (adhesive strength before heating) was measured using a tensile tester (Tensilon: manufactured by Orientec Co., Ltd.) in accordance with JIS Z0237 at a peel speed of 300 mm / min and a peel angle of 180°. The evaluation criteria are as follows. [Evaluation Criteria] ◎: 10N / 25mm or more, excellent. ◎○8N / 25mm or more and less than 10N / 25mm, very good. ○: 7N / 25mm or more but less than 8N / 25mm, good. △: 3N / 25mm or more but less than 7N / 25mm, usable. ×: Less than 3N / 25mm, not practical.
[0095] <Conformity to uneven surfaces> The decorative sheet obtained above was attached to the frame of a TOM molding machine (NGF molding machine, manufactured by Fuse Vacuum Co., Ltd.), and then a melamine plate with a width of 7 cm and a length of 15 cm was set inside the frame, and a square pyramid-shaped PP resin with a top side of 20 mm, a bottom side of 40 mm, and a height of 15 mm was set on top of the melamine plate. The melamine plate and the PP resin were then molded to cover the decorative sheet, and a decorative structure was obtained. The surface condition after molding was evaluated based on the following evaluation criteria. (Evaluation Criteria) : No lifting or peeling was observed on any surface. Very good. ○: No lifting is observed on the uneven surface, but some peeling occurs at the edge. Good. △: Some lifting was observed on uneven surfaces, and peeling occurred at the edges. Practical use is possible. ×: Lifting occurred on all uneven surfaces, and peeling occurred on the entire surface. Not practical.
[0096] <Durability after molding> The decorative structure obtained in the unevenness-following test was left for 24 hours in an atmosphere of 23°C and 50% RH, after which a 5cm-long cross was made on the surface of the molded product, and the product was left for 168 hours in a high temperature or high temperature and high humidity environment (60°C / 100°C / 80°C-95% RH), after which it was evaluated for lifting, peeling, and displacement based on the following evaluation criteria. (Evaluation Criteria) ◎: No lifting or peeling, but misalignment of less than 0.5 mm occurred. Excellent. ◎○: No lifting or peeling, but misalignment of 0.5 mm to less than 1 mm occurred. Very good ○: No lifting or peeling, but misalignment of 1 mm or more and less than 3 mm occurred. Good. △: No lifting or peeling, but misalignment of 3 mm to less than 10 mm occurred. Usable. ×: Lifting or peeling occurs, or deviation of 10 mm or more occurs. Not practical.
[0097] <Appearance after durability test> The obtained adhesive composition was applied to the release-treated surface of a polyethylene terephthalate (PET) film (thickness 38 μm) with one side subjected to release treatment so that the thickness after drying was 25 μm. Then, after drying at 105 ° C for 2 minutes, the coating film was attached to a commercially available polyethylene terephthalate (PET) film (thickness 50 μm) and aged for 7 days under an atmosphere of 23 ° C-50% RH to prepare an adhesive sheet. A test piece having a width of 15 mm and a length of 30 mm was cut out from the adhesive sheet. The release sheet was peeled off from the cut adhesive sheet, and the exposed adhesive layer was attached to the surface of a slide glass and pressed by rolling a 2 kg roll back and forth once. Thereafter, the test piece was left in an atmosphere of 80 ° C-95% RH for 168 hours, and the removed test piece was left in an atmosphere of 23 ° C-50% RH for another 24 hours, after which the haze was measured with a haze meter (manufactured by Nippon Denshoku Kogyo Co., Ltd.). ◎: Haze less than 7, excellent. ◎○: Haze 7 or more but less than 8, very good. ○: Haze 8 or more but less than 9, good. △: Haze 9 or more but less than 12, usable. ×: HAZE 12 or above, not practical.
[0098] [Table 2]
[0099] The abbreviations in Table 2 are as follows: TETRAD-X: Epoxy crosslinking agent (Mitsubishi Gas Chemical Company, Inc., N,N,N',N'-tetraglycidyl-m-xylylenediamine) [Tackifier resin] Alcon P-90: Hydrogenated petroleum resin (softening point 90°C) manufactured by Arakawa Chemical Industries, Ltd. Petcol LX: Aromatic petroleum resin (softening point 98°C) manufactured by Tosoh Corporation FTR6100: Aliphatic / aromatic petroleum resin (softening point 95°C) manufactured by Mitsui Chemicals, Inc. FTR8120: Aromatic petroleum resin (softening point 120℃) manufactured by Mitsui Chemicals, Inc. YS Polystar T115: Terpene phenol resin (softening point 115°C) manufactured by Yasuhara Chemical Co., Ltd. Pencel D-125: Rosin resin (softening point 125°C) manufactured by Arakawa Chemical Industries, Ltd. Super Ester A-75: Rosin resin (softening point 75°C) manufactured by Arakawa Chemical Industries Co., Ltd. SYLVALITE2038: Rosin-based resin (softening point 37°C) manufactured by Kraton Polymers Pencel D-160: Rosin resin (softening point 157.5°C) manufactured by Arakawa Chemical Industries, Ltd.
[0100] [Table 3]
[0101] The present invention is not limited to the above-described embodiment and examples, and appropriate design changes are possible without departing from the spirit of the present invention.
[0102] The pressure-sensitive adhesive compositions of the present invention were excellent in adhesive strength, conformability to irregularities, durability after molding, and coating appearance, as shown in Examples 1 to 27 in Table 3. In contrast, Comparative Examples 1 to 3 in Table 3 did not satisfy all of the above physical properties. The composition having the above-mentioned excellent properties can be suitably used for decoration of, for example, aircraft, automobiles, railways, interior and exterior building materials, nursing and medical fields, electrical appliances, etc., and its use is not particularly limited, but it is preferably used for automobile interior and exterior parts, home appliances, smartphones, and housing building materials, more preferably used for automobile interior and exterior parts and housing building materials, and particularly preferably used for automobile interior and exterior parts. In addition, as a method for decoration using a decorative sheet, insert molding method, in-mold molding method, vacuum molding method, vacuum pressure molding method, etc. are known, and although it is not particularly limited, the method using vacuum molding method and vacuum pressure molding method is particularly preferred.
Claims
1. A pressure-sensitive adhesive composition for decorative sheets, comprising a (meth)acrylic acid ester copolymer (A), a curing agent (B) and a tackifier resin (C) having a softening point of less than 130°C, the composition containing 2 parts by mass or more and 60 parts by mass or less of the tackifier resin (C) per 100 parts by mass of the (meth)acrylic acid ester copolymer (A).
2. The (meth)acrylic acid ester copolymer (A) is a copolymer of a monomer mixture containing any two or more selected from the group consisting of the following (a1), (a2), and (a3), and the total content of (a1), (a2), and (a3) is 75 mass% or more in 100 mass% of the monomer mixture. (a1): A (meth)acrylic acid alkyl ester monomer having a homopolymer glass transition temperature of 0° C. or lower and an alkyl group having 4 to 8 carbon atoms. (a2): (meth)acrylic acid alkyl ester monomer having an alkyl group with 1 to 3 carbon atoms (a3): Vinyl ester monomer of a carboxylic acid having an alkyl group having 1 to 3 carbon atoms
3. 2. The pressure-sensitive adhesive composition for decorative sheets according to claim 1, wherein the tackifier resin (C) contains at least one of a terpene resin and a synthetic hydrocarbon resin.
4. The pressure-sensitive adhesive composition for decorative sheets according to claim 1 , which is used for attachment to an adherend by a vacuum forming method or a vacuum / pressure forming method.
5. A decorative sheet comprising a substrate and an adhesive layer made of the adhesive composition for decorative sheets according to any one of claims 1 to 4.
6. A decorative structure comprising an adherend and the decorative sheet according to claim 5 .
7. A method for producing a decorative structure, comprising forming the decorative structure according to claim 6, in which the decorative sheet is integrated with the adherend by vacuum forming or vacuum / pressure forming.
Citation Information
Patent Citations
Interior material for automobile
JP2005178637A
Decorative film for vacuum forming, decorative molding, and method for producing the same
JP2012213894A
Adhesive for optical use, adhesive sheet for optical use, and image display device using the same
JP2015013925A
Adhesive composition for decorative film, decorative film and decorative molding
JP2018158990A
Adhesive composition for decorative sheet
JP2023092116A